Yo sup??
we can solve this question by applying trigonometric ratios
cos59=CB/CD
CD=CB/cos59
=7.76
=7.8
Hope this helps.
<span>Using
the points (2, 45) (4, 143) and (10, 869), we can plug them into the
following system of 3 equations using the y = ax^2 + bx + c format:
45 = a(2)^2 + b(2) + c
143 = a(4)^2 + b(4) + c
869 = a(10)^2 + b(10) + c
which simplifies to:
45 = 4a + 2b + c
143 = 16a + 4b + c
869 = 100a + 10b + c
Solving the system, we get a = 9, b = -5, and c = 19. Thus the equation is:
c(x) = 9x^2 - 5x + 19
If you have a TI graphing calculator, you can also enter the points by
pressing Stat -> Edit and enter (2, 45) (4, 143) and (10, 869) into
it. Go back and calculate the QuadReg of the points from the Calc tab
and it will give you the same answer.
Now that we know the function that will produce the price of production
for any number of calculators, plug in x = 7 and it will give you the
price to produce 7 calculators.
c(x) = 9x^2 - 5x + 19
==> c(7) = 9(7)^2 - 5(7) + 19
==> c(7) = 441 - 35 + 19
==> c(7) = 425
Therefore, it costs $425 to produce 7 calculators.
Hope this helps.
</span>
Answer:
36
Step-by-step explanation:
6^2 = 6 × 6
----------------
6×6 = 36
Answer:
The answer is 2
Step-by-step explanation:
Rate of change of function is given by :
![\frac{(f(x_{2})-f(x_{1}))}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=%5Cfrac%7B%28f%28x_%7B2%7D%29-f%28x_%7B1%7D%29%29%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
For function y = 6,
rate of change =
![=\frac{(f(x_{2})-f(x_{1}))}{x_{2}-x_{1}}\\=\frac{6-6}{x_{2}-x_{1}}\\=0](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%28f%28x_%7B2%7D%29-f%28x_%7B1%7D%29%29%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%3D%5Cfrac%7B6-6%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%3D0)
because the function is independent of x.
For function y = 2·x + 7,
rate of change =
![=\frac{(f(x_{2})-f(x_{1}))}{x_{2}-x_{1}}\\=\frac{2\cdot x_{2}+7-2\cdot x_{1}-7}{x_{2}-x_{1}}\\=\frac{2\cdot x_{2}-2\cdot x_{1}}{x_{2}-x_{1}}\\=\frac{2\cdot (x_{2}-x_{1})}{x_{2}-x_{1}}\\=2](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%28f%28x_%7B2%7D%29-f%28x_%7B1%7D%29%29%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%3D%5Cfrac%7B2%5Ccdot%20x_%7B2%7D%2B7-2%5Ccdot%20x_%7B1%7D-7%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%3D%5Cfrac%7B2%5Ccdot%20x_%7B2%7D-2%5Ccdot%20x_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%3D%5Cfrac%7B2%5Ccdot%20%28x_%7B2%7D-x_%7B1%7D%29%7D%7Bx_%7B2%7D-x_%7B1%7D%7D%5C%5C%3D2)
So, the rate of change of 2 is greater than rate of change of function 1 by 2 - 0 = 2.